Non-fluorinated hybrid PAEK / heterocyclic thermoplastic / silicone resin coating

By using a thermoplastic polymer mixture with high thermomechanical properties as a sub-layer in the non-stick coating of the cooking utensil, the problem of insufficient mechanical strength of the non-stick coating in the prior art at high temperatures is solved, and higher scratch resistance and peel resistance are achieved.

CN119604216APending Publication Date: 2025-03-11SEB SA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056006.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The non-stick coating of existing cooking utensils is insufficient mechanical strength at high temperatures, resulting in easy scratching and peeling.

Method used

A thermoplastic polymer mixture based on high thermomechanical properties is used as a sublayer, including polyaryletherketone (PAEK), polyetherimide (PAI), polyimide (PI) and polybenzimidazole (PBI), and is deposited on the metal substrate by spraying, roll coating and other technologies.

Benefits of technology

It improves scratch resistance and peel resistance of the non-stick coating to ensure that good non-stick properties can be maintained under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604216A_ABST
    Figure CN119604216A_ABST
Patent Text Reader

Abstract

The invention relates to a coated cooking element (1) for a cooking appliance or an electric cooking appliance, comprising a metal substrate (2) which is coated on at least one face (2a) with at least the following layers and which, in the following order starting from the metal substrate (2): (3a) connecting sub-layers, a sublayer comprising between 20% and 100% by weight, based on the total weight of the sublayer, of one or more polymers (alpha) selected from the group consisting of polyaryletherketones (PAEK) and one or more polymers selected from the group consisting of polyetherimides (PEI), polyimides (PI), polyamide-imides (PAI) and polybenzimidazoles (PBI) wherein the PAEK: (PEI + PI + PAI + PBI) weight ratio is comprised between 1: 1 and 15: 1; (3b) optionally, one or more intermediate layers consisting of one or more colorants and optionally one or more silicone resins, one or more thermoplastic polymers and / or one or more fillers, and / or one or more additives, (3c) a finish layer consisting of one or more silicone resins and optionally one or more thermoplastic polymers, and / or one or more fillers, and / or one or more additives, and / or flakes; the invention also relates to a manufacturing method thereof and a cooking utensil containing the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention is applicable to the field of non-stick coatings for cooking surfaces of cooking utensils and electric cooking appliances. Background Art

[0002] Polytetrafluoroethylene (PTFE) coated cookware is popular in the market because they allow cooking with little or no added fat and are easy to maintain. However, an inherent weakness of these coatings is their low mechanical strength, especially at high temperatures.

[0003] To address this, many technical solutions have been proposed, among which are strengthening the coating with hard fillers or inserting hard sublayers of inorganic or organic type.

[0004] In the case of primers reinforced with hard organic or inorganic fillers, abrasion resistance does improve significantly, but impacts on the metal are also observed when cooking food such as pork chops or when using a metal spatula.

[0005] In the case of inorganic hard substrates, such as those made of enamel or metal oxides, wear resistance is further improved and the impact problem is limited but not eliminated.

[0006] Organic polymer sublayers are also known. These sublayers effectively make it possible to significantly reduce the occurrence of scratches or even eliminate them. This strategy is therefore very interesting. The polymers used are usually thermoplastics with high heat resistance and high melting points, such as polyaryletherketones, in particular poly(oxy-1,4-phenylene-1,4-phenylene-carbonyl-1,4-phenylene or PEEK, or phenylene sulfides.

[0007] PEEK is very interesting in cookware due to its high melting point (343°C) and excellent thermal stability under usage conditions of 260°C.

[0008] Sublayers from such polymers can be obtained by the following coating techniques: spraying, roller coating, curtain coating, pad printing, screen printing, thermal spraying, electrostatic spraying, inkjet.

[0009] Application WO 2000 / 54895 mentions the use of a sublayer consisting solely of PEEK (particle size between 5 μm and 100 μm, D50 preferably 20 μm) deposited on a metal substrate, covering 60% to 95% of the utensil surface, then covered with a single or multilayer non-stick coating based on fluorinated resins and fluorinated copolymers. The PEEK sublayer is deposited by pad printing or screen printing or spraying in the form of a dispersion.

[0010] The thickness of this PEEK layer is comprised between 5 μm and 100 μm.

[0011] The disadvantage of the above method is the need for a secondary cure of the PEEK-based fluorinated coating. The first cure requires a temperature above the melting point of the polymer constituting the sublayer (i.e. between 380 and 400°C for PEEK) to make it adhere to the metal substrate. The tool must then be cooled significantly, which is very expensive in terms of time and energy, but is essential in order to be able to apply a continuous fluorinated layer that will be sintered during the second cure at high temperature (>420°C).

[0012] Application WO 2010 / 130954 describes a hard sublayer forming a continuous network, which is deposited discontinuously on the inner bottom of a cooking utensil. The material constituting the layer is a ceramic (alumina-titanium mixture) or a metal or a polymer (PAI, PEI, PI, PES, PPS, PEK or PEEK). The surface area of ​​the cooking utensil covered by this material is comprised between 30% and 80%, the size between the deposited droplets being comprised between 2 μm and 50 μm. The surface roughness Ra of the hard layer is comprised between 2 μm and 12 μm, preferably between 4 μm and 8 μm.

[0013] This material is applied in powder form by a flame spraying process, the particle size preferably being comprised between 20 μm and 45 μm.

[0014] Prior to the process of depositing the powder by flame spraying, the metal substrate must be preheated to above 180°C.

[0015] The fluorinated layer was deposited by spraying after the deposition cooled to room temperature, followed by a primary sintering at 430°C.

[0016] Patent FR 2871038 mentions the use of a PEEK sublayer, depositing a PAI resin and a fluorinated resin on a metal substrate, then covered with one or more layers of non-stick coating, the PEEK not being present in these upper layers.

[0017] This sublayer consists of a mixture of PAI, PEEK and PTFE, such that PTFE is comprised between 9 and 15% by weight and PAI is comprised between 4 and 5% by weight.

[0018] In all cases, the dry matter content of PEEK in the final fluorinated film is about 0.12% to 1.1% by weight, preferably 0.12% to 0.9% by weight.

[0019] The particle size D50 of the PEEK powder is 5 to 35 μm.

[0020] In all cases, the first coating contains a fluorinated resin.

[0021] This liquid coating is deposited by spraying. Then an upper layer of a fluorinated coating, which also contains one or more bonding primers, is deposited by spraying. These layers are sintered by a single cure at 400-420°C.

[0022] The disadvantage of this coating method is that the content of PEEK resin in the first layer is very low and does not achieve sufficient mechanical properties to have a scratch-resistant coating.

[0023] Application WO 00 / 054896 mentions the use of a fluorinated resin-free PEEK sublayer consisting of at least 50% by weight of PEEK powder, the surface covered by PEEK thus being comprised between 60% and 95% of the surface of the tool.

[0024] The primer contains at least 50% PEEK and may also contain a mixture with other pure heat-stable resins or mixed heat-stable resins, such as polyphenylene sulfide (PPS), polyetherimide (PEI), polyimide (PI), polyetherketone (PEK), polyethersulfone (PES), and polyamideimide (PAI).

[0025] It may also contain fillers chosen from metal oxides: silica, mica or plate-like fillers. It does not include any fluorinated resins.

[0026] The first curing is performed at an elevated temperature of at least 260° C., preferably greater than or equal to 340° C. to melt the PEEK.

[0027] PEEK is in powder form with a particle size between 4 μm and 80 μm, and a D50 of preferably 20 μm. The thickness of this sub-layer is comprised between 5 μm and 100 μm.

[0028] This liquid coating is deposited by spraying. Then an upper layer of a fluorinated coating or a primer with a fluorinated topcoat is sprayed. All these layers are sintered in a second cure between 400°C and 420°C to sinter the fluorinated coating.

[0029] US 6,596,380 B1 mentions a scratch-resistant fluorinated coating, the first layer of which contains at least 50% by weight of PEEK (preferably between 60% and 95%), mixed with a thermally stable polymer resin such as PPS, PEI, PI, PAI and mixtures thereof and fillers such as metal oxides, silica, mica, and does not contain any fluorinated resin. The thickness of the first layer is comprised between 5 and 100 μm.

[0030] PEEK is a powder with a particle size of 4 μm to 80 μm and a D50 of about 20 μm.

[0031] However, the method of obtaining such a coating necessarily involves a secondary curing / sintering at between 400 and 420°C.

[0032] Pure silicone resins have non-stick properties and can withstand temperatures above 220-230° C. In contrast, they are considered to have poor adhesion to substrates.

[0033] In contrast, silicone-polyester resins are very widely used in the molding industry, since they are non-sticky when adhered to a substrate and are compatible with stamping processes. However, they degrade at temperatures above 230°C. In fact, the temperature range for use in cookware is between 50 and 250°C, and it is not uncommon to reach temperatures of 300°C or even 350°C in the case of appliances with induction bottoms. Their use is therefore incompatible with the temperatures of use in the cookware sector.

[0034] The present invention relates to the technical problem of improving the scratch resistance and peeling resistance of silicone coatings by producing a sublayer based on a thermoplastic polymer mixture having high thermomechanical properties in contact with the metal substrate.

[0035] definition

[0036] For the purposes of the present invention, the term "layer" should be understood as a continuous or discontinuous layer. A continuous layer (also called an integral layer) is a single entity forming an entire solid block that completely covers the surface on which it is laid. A discontinuous layer (or non-integral layer) may consist of several parts and is therefore not a single entity.

[0037] The terms "base layer", "primer layer", "adhesion layer" or "adhesion primer" are understood to mean all layers from the first layer applied directly to the support (preferably this layer adheres well to the substrate and contributes all its mechanical properties: hardness, scratch resistance) to the last layer before the first decorative layer.

[0038] The term "finishing layer" or "finishing" is understood to mean a continuous and transparent surface layer which leaves the decorative layer completely visible while protecting it from mechanical damage and giving the coating its non-stick properties. Preferably, the final finishing layer is intended to come into contact with food.

[0039] The term "decoration" or "decorative layer" is understood to mean one or more continuous or discontinuous layers comprising a pigment composition. The finish may be in the form of one or more patterns and one or more colors. The decoration is clearly visible to the naked eye for the user and is clearly visible at the usual distances at which the household article is used.

[0040] The term "overlapping layers" is understood to mean partially or completely overlapping layers. The layers may be in the form of partially overlapping patterns, such as concentric disks.

[0041] The term "adjacent layers" is understood to mean non-overlapping layers. These coatings may be in the form of identical or different non-overlapping patterns, preferably uniformly distributed.

[0042] The term "reference temperature pigment composition" is understood to mean a composition comprising a pigment which, at a given temperature, indicates to the user that the optimum use temperature has been reached. This indication is made by comparing the color of the thermochromic pigment composition with the color of the reference temperature pigment composition. Either the optimum use temperature is reached when the colors are identical, or when the colors are visually very different.

[0043] A "reference temperature pigment composition" may include a pigment having:

[0044] - the same color as the thermochromic pigment composition at the optimum use temperature,

[0045] * Because at room temperature the pigment has the same color as the thermochromic pigment composition at the optimal use temperature and does not change color with temperature,

[0046] * or because the pigment has a different color at room temperature than a thermochromic pigment composition that becomes the same color as the thermochromic pigment composition at the optimal use temperature,

[0047] - A colour which is substantially different from the colour of the thermochromic pigment composition at the optimum use temperature, whether or not the pigment changes colour with changes in temperature.

[0048] The optimum use temperature is reached when the color of the reference temperature pigment composition corresponds to the color indicated in the user guide of the household article comprising the coating according to the invention or to the color indicated on a color scale provided to the user together with the article.

[0049] The reference temperature pigment composition is thermochromic or thermally stable.

[0050] The reference temperature pigment composition may be, for example, a cooking reference temperature pigment composition or used to indicate a risk of overheating.

[0051] The present invention has at least one of the following advantages:

[0052] - the coating according to the invention has a thermochromic function with a clearly visible, contrasting color change in the target and core temperature range, for example around the cooking temperature of the food in the cooking vessel;

[0053] - when cooking food, the coating according to the invention can provide good temperature control, which is necessary for health and taste reasons, but also for safety and to limit overheating at points that weaken the coating;

[0054] - the thermochromic properties of the thermochromic pigment composition are reversible, which means that after a color change under the action of heat, when the temperature is lowered, the compound returns to its initial state and its initial color; this color change cycle (reversibility) can be repeated indefinitely;

[0055] The coating according to the invention has a high thermal stability during elevated temperatures; it is stable up to about 450°C.

[0056] For the purposes of the present invention, the expression "thermochromic semiconductor" should be understood to mean an inorganic or organic compound that exhibits a reversible color change when the temperature rises. The gradual and reversible thermochromic properties of these semiconductor compounds are related to the reduction of the semiconductor band gap width caused by the expansion of the material. In fact, the periodicity of the network of anions and cations causes the energy levels to aggregate into energy bands. The energy band filled with higher energy is called the valence band, while the empty energy band with lower energy is called the conduction band. Between these two bands, there is a forbidden band called a band gap. The color of the semiconductor material can originate from the presence of charge transfer, which corresponds to the passage of electrons from the valence band to the conduction band on the same atom, or generally from the orbit of anions to the orbit of cations (interatomic photon absorption).

[0057] In the fields of application foreseen by the invention, optimal conditions are obtained when the coating reaches a temperature suitable for cooking food, preferably between 100 and 250°C.

[0058] For the purposes of the present invention, "thermochromic pigments or pigment compositions" are understood to mean pigments or pigment compositions that change color with temperature within a given temperature range, the change being reversible. This color change is visible to the user with the naked eye and at a normal distance of use.

[0059] The term "thermally stable pigment" is understood to mean a pigment that does not show a color change when subjected to an increase in temperature within a given temperature range, or a pigment that shows a color change when subjected to an increase in temperature within a given temperature range that is so low as to be invisible to the user with the naked eye and not visible at normal use distances.

[0060] Preferably, the color difference ΔE* of the heat-stable pigment between 25°C and 200°C is less than 10, ΔE* being defined in the CIELAB color space by the CIE 1976 formula:

[0061]

[0062] L1*, a1* and b1* characterize the L*a*b* values ​​of the compounds at room temperature.

[0063] L2*, a2* and b2* characterize the L*a*b* values ​​of the compounds at 200°C.

[0064] The expression "same color" shall mean that they are indistinguishable by the user with the naked eye and at a distance of ordinary use.

[0065] For the purposes of the present invention, the expression "cooking utensil" should be understood to mean an object intended for cooking. For this purpose, it is intended to be subjected to a heat treatment.

[0066] For the purposes of the present invention, the expression "article for heat treatment" is to be understood as an article to be heated by an external heating system, such as frying pans, deep-frying pans, woks, stir-fry pans and barbecue grills, and which is capable of transferring the heat provided by the external heating system to the material or food in contact with said article.

[0067] For the purposes of the present invention, the expression "electric cooking appliance" should be understood as a heating object having its own heating system, for example an electric griddle, an electric raclette appliance, an electric fondue appliance, an electric grill, an electric frying pan, an electric rice cooker, a bread maker or an electric pressure cooker.

[0068] A "silicone resin-based coating" is understood to mean a coating which comprises one or more silicone resins in one or more of its layers.

[0069] "Coating" is understood to mean all layers that adhere to the metal substrate and cover the substrate. The coating obtained according to the invention is advantageously solid. "Solid" is understood to mean the property of a viscous material that is insoluble in water, in common solvents, in food components such as aqueous or fatty mixtures, even if the material may be very hard or very flexible, such as an elastomer.

[0070] In the present invention, the wt. % values ​​are expressed on a dry basis, ie without solvent. Summary of the invention

[0071] A first object of the invention relates to a coated cooking element (1) for a cooking utensil or electric cooking utensil, comprising a metal substrate (2) coated on at least one face (2a) with at least the following layers, in order starting from the metal substrate (2):

[0072] (3a) an adhesive sublayer comprising between 20 wt% and 100 wt% of one or more polymers (α) selected from the group consisting of polyaryletherketone (PAEK) and one or more polymers selected from the group consisting of polyetherimide (PEI), polyimide (PI), polyamide-imide (PAI) and polybenzimidazole (PBI), based on the total weight of the sublayer, wherein the weight ratio of PAEK:(PEI+PI+PAI+PBI) is comprised between 1:1 and 15:1;

[0073] (3b) optionally one or more intermediate layers, said intermediate layers consisting of one or more colorants and optionally:

[0074] - one or more silicone resins, and / or

[0075] - one or more thermoplastic polymers; and / or

[0076] - one or more fillers; and / or

[0077] - One or more additives.

[0078] (3c) a finishing layer, the finishing layer consisting of one or more silicone resins and optionally:

[0079] - one or more thermoplastic polymers; and / or

[0080] - one or more fillers; and / or

[0081] - one or more additives; and / or

[0082] - Thin flakes.

[0083] Another object of the present invention relates to a method for manufacturing a coated cooking element (1) according to the invention, characterized by the following steps:

[0084] i. A step of supplying a metal substrate (2) comprising two opposing surfaces;

[0085] ii. Optionally, a step of treating the face (2a) of the substrate (2) to obtain a treated face (2a) that promotes adhesion of the adhesive sublayer (3a) to the substrate (2);

[0086] iii. depositing one or more continuous layers of an adhesive sublayer (3a) on the face (2a) of the substrate (2);

[0087] iv. Optionally, drying and / or sintering at a temperature of> 400°C;

[0088] v. Optionally, applying a layer (3ab) and / or an intermediate layer (3b);

[0089] vi. Applying a finishing layer (3c);

[0090] vii. Drying at a temperature of 230°C to 420°C.

[0091] Another object of the present invention relates to a cooking utensil (100) comprising a coated cooking element (1) according to the present invention.

[0092] Another object of the present invention also relates to an electric cooking appliance (200) comprising a coated cooking element (1) according to the present invention and a heating source (210) configured to heat the coated cooking element (1). BRIEF DESCRIPTION OF THE DRAWINGS

[0093] [ Figure 1 ]: Diagram of a cooking element according to the invention, wherein layer (3b) is continuous and covers the entire layer (3a).

[0094] [ Figure 2 ]: Figure of a cooking element according to the invention, in which layer (3b) does not cover the entire layer (3a) and forms a decoration.

[0095] [ Figure 3 ]: Figure of a cooking element according to the invention, wherein the layer (3b) comprises two decorations (i) and (j).

[0096] [ Figure 4 ]: Pattern distribution diagram. 4A = adjacent, non-overlapping patterns. 4B = partially overlapping patterns. 4C = overlapping patterns. .

[0097] [ Figure 5 ]: Illustration of a cooking appliance according to the present invention.

[0098] [ Figure 6 ]: Illustration of an electric cooking appliance according to the present invention. DETAILED DESCRIPTION

[0099] A first object of the invention relates to a coated cooking element (1) for a cooking utensil or electric cooking utensil, comprising a metal substrate (2) coated on at least one face (2a) with at least the following layers, in order starting from the metal substrate (2):

[0100] (3a) an adhesive sublayer comprising between 20 wt% and 100 wt% of one or more polymers (α) selected from the group consisting of polyaryletherketone (PAEK) and one or more polymers selected from the group consisting of polyetherimide (PEI), polyimide (PI), polyamide-imide (PAI) and polybenzimidazole (PBI), based on the total weight of the sublayer, wherein the weight ratio of PAEK:(PEI+PI+PAI+PBI) is comprised between 1:1 and 15:1;

[0101] (3b) optionally one or more intermediate layers, preferably two intermediate layers, consisting of one or more colorants and optionally:

[0102] - one or more silicone resins, and / or

[0103] - one or more thermoplastic polymers; and / or

[0104] - one or more fillers; and / or

[0105] - One or more additives.

[0106] (3c) a finishing layer, the finishing layer consisting of one or more silicone resins and optionally:

[0107] - one or more thermoplastic polymers; and / or

[0108] - one or more fillers; and / or

[0109] - one or more additives; and / or

[0110] - Thin flakes.

[0111] Advantageously, the layer (3a) and the optional layers (3b) and (3c) form a coating (3) coating the metal substrate (2). The coating (3) has non-stick properties and forms a non-stick coating.

[0112] Advantageously, the layer ( 3 a ) is in contact via one of its faces with the metal substrate ( 2 ) via its face ( 2 a ).

[0113] Thus, at least one coated face (2a) of the metal substrate is a cooking surface. In other words, the coating of the cooking element (1) according to the invention is intended to come into contact with food.

[0114] The coating of the cooking element (1) according to the invention does not contain fluoropolymers. In other words, the coating is or is free of fluoropolymers.

[0115] The coating of the cooking element (1) according to the invention is intended to come into contact with food.

[0116] Advantageously, the finishing layer (3c) is in contact with the food through one of its faces and thus forms a cooking surface (5).

[0117] Advantageously, the thickness of the layer ( 3 b ) is comprised between 1 μm and 100 μm, preferably between 2 μm and 30 μm, particularly preferably between 3 μm and 10 μm.

[0118] Advantageously, the thickness of the layer ( 3 c ) is comprised between 0.05 μm and 100 μm, preferably between 0.08 μm and 20 μm, particularly preferably between 0.1 μm and 10 μm.

[0119] According to one embodiment, the thickness of the layer (3c) is comprised between 0.1 μm and 2 μm, preferably between 0.2 μm and 1.5 μm. In a particular embodiment of the invention, the thickness of the layer (3c) is 100 nm + / - 5 nm.

[0120] According to another embodiment, the thickness of the layer ( 3 c ) is comprised between 10 μm and 100 μm, preferably between 20 μm and 85 μm, particularly preferably between 30 μm and 70 μm.

[0121] The coating of the cooking element (1) according to the invention may comprise one or more layers (3ab), optionally interposed between the layer (3a) and the layer (3b) or between the layer (3a) and the layer (3c), and the one or more layers are composed of one or more silicone resins and optionally:

[0122] - one or more thermoplastic polymers; and / or

[0123] - one or more fillers; and / or

[0124] - One or more additives.

[0125] Advantageously, the thickness of the layer ( 3ab ) is comprised between 0.05 μm and 100 μm, preferably between 0.08 μm and 20 μm, particularly preferably between 0.1 μm and 10 μm.

[0126] Adhesive sublayer (3a)

[0127] Advantageously, the adhesive sublayer (3a) comprises one or more polymers (β) selected from the group consisting of polyphenylene sulfide (PPS) and polyethersulfone (PES), preferably in an amount of at least 20% by weight, preferably at least 25% by weight, of the total weight of the sublayer of one or more polymers selected from the group consisting of polyphenylene sulfide (PPS) and polyethersulfone (PES).

[0128] Advantageously, the adhesive sublayer (3a) represents less than 40% by weight, preferably less than 30% by weight, preferably between 5 and 25% by weight of the total weight of the filler sublayer.

[0129] Advantageously, the adhesive sublayer (3a) comprises one or more acrylic resins. The acrylic resins are advantageously selected from polymers obtained by emulsion polymerization of various monomers with other acrylic acid-based monomers.

[0130] Advantageously, the adhesive sublayer (3a) comprises one or more colorants.

[0131] Advantageously, the colorant of the bonding sublayer (3a) represents less than 30% by weight, preferably less than 20% by weight, of the total weight of the sublayer.

[0132] Advantageously, the polyaryletherketone (PAEK) is selected from the group consisting of polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK).

[0133] Advantageously, the polymer (α) is selected from the group consisting of polyetheretherketone (PEEK) and polyamideimide (PAI).

[0134] Advantageously, when polymer (α) represents 20 to 40% of the sub-layer according to the invention, the PAEK:(PEI+PI+PAI+PBI) weight ratio is comprised between 6:1 and 12:1.

[0135] Advantageously, when polymer (α) represents 40 to 80% of the sub-layer according to the invention, the PAEK:(PEI+PI+PAI+PBI) weight ratio is comprised between 12:1 and 15:1.

[0136] Advantageously, polymer (α) represents from 25 to 40%, preferably from 25 to 35%, of the total weight of the sublayer.

[0137] The weight ratio of polymer (α) to polymer (β) is advantageously comprised between 2:5 and 2:3, preferably between 1:2 and 1:3.

[0138] Advantageously, the polyaryletherketone (PAEK) is selected from the group consisting of polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK), particularly preferably PEEK.

[0139] Advantageously, polymer (α) is selected from the group consisting of polyaryletherketones (PAEK) and polyamideimides (PAI) and mixtures thereof. It is particularly preferred that part (α) is a mixture of PAEK and PAI polymers.

[0140] Advantageously, polymer (α) is selected from the group consisting of polyetheretherketone (PEEK) and polyamideimide (PAI) and mixtures thereof. It is particularly preferred that part (α) is a mixture of PEEK and PAI polymers.

[0141] Advantageously, polymer (β) is polyethersulfone (PES).

[0142] In a preferred embodiment of the present invention, parts (α) and (β) are a mixture of PEEK, PAI and PES polymers.

[0143] Advantageously, the adhesive sublayer (3a) may also contain one or more solvents, preferably polar aprotic solvents, preferably unlabeled, such as N-formylmorpholine (NFM), N-methylimidazole (NMI), N-butylpyrrolidone (NBP) and dimethyl sulfoxide (DMSO), or alcohol solvents, such as propylene glycol (PPG) and diethylene glycol.

[0144] Advantageously, the adhesive sublayer (3a) may comprise one or more surfactants.

[0145] Advantageously, the adhesive sublayer (3a) may also contain one or more defoaming agents.

[0146] In a preferred embodiment of the present invention, the adhesive sublayer (3a) is a mixture of PEEK, PAI, PES and optionally fillers, acrylic resins and colorants.

[0147] The thickness of the adhesive sublayer ( 3 ) is advantageously comprised between 10 and 100 μm, preferably between 20 and 80 μm, preferably between 30 and 60 μm.

[0148] Metal substrate

[0149] Advantageously, the metal substrate (2), also called carrier, is a substrate made of aluminum, stainless steel, cast iron or cast aluminum, iron, titanium or copper.

[0150] For the purposes of the present invention, aluminum is understood to be a metal consisting of 100% aluminum or an aluminum alloy.

[0151] Advantageously, the metal substrate (2) is an aluminum substrate, a stainless steel substrate or a multilayer metal substrate. The metal substrate (2) can be a two-layer or three-layer substrate, which can be obtained by, for example, co-lamination, by solid-state bonding or by thermal or cold shock bonding.

[0152] Preferably, the metal substrate (2) comprises alternating layers of metals and / or metal alloys.

[0153] According to one embodiment, the metal substrate (2) is an aluminum alloy substrate, a stainless steel substrate, or a multi-layer metal substrate having an aluminum alloy or stainless steel surface (2a).

[0154] Preferably, the metal substrate (2) is an aluminum substrate.

[0155] Advantageously, the thickness of the metal substrate (2) is comprised between 0.5 mm and 10 mm.

[0156] Advantageously, the face ( 2 a ) of the metal substrate ( 2 ) has previously undergone a surface treatment so as to improve the adhesion of the coating to said substrate.

[0157] According to one embodiment, the surface of the face (2a) of the metal substrate (2) has undergone a surface treatment which is a physicochemical treatment of the chemical etching, brushing, hydration, sandblasting, shot blasting, plasma, corona or laser type, chemical activation or a combination of these different techniques.

[0158] Advantageously, the face (2a) of the substrate on which the coating (3) according to the invention is to be applied can be treated to increase its specific surface; for aluminium substrates, this treatment can be carried out by anodising (producing a tubular aluminium oxide structure), by chemical etching, sandblasting, brushing, shot peening or by adding material using techniques such as thermal spraying (flame, plasma or arc spraying). Other metal substrates can also be polished, sandblasted, brushed, micro-bead blasted or receive added material using techniques such as thermal spraying (flame, plasma or arc spraying).

[0159] Metal substrates that can be used in the present invention advantageously include anodized or non-anodized aluminum substrates, optionally polished, brushed, sandblasted, shot blasted or micro-bead blasted, anodized or non-anodized aluminum alloy substrates, optionally polished, brushed, sandblasted or micro-bead blasted, steel substrates, optionally polished, brushed, sandblasted, shot blasted or micro-bead blasted, stainless steel substrates, optionally polished, brushed, sandblasted or micro-bead blasted, cast steel substrates, aluminum or iron substrates, copper substrates, optionally hammered or polished.

[0160] Advantageously, the substrate can be chosen from a substrate comprising a ferritic stainless steel / aluminium / austenitic stainless steel layer, a substrate comprising a stainless steel / aluminium / copper / aluminium / austenitic stainless steel layer, a shell made of cast aluminium, aluminium or an aluminium alloy lined with an external stainless steel bottom, a metal co-laminated substrate, such as a two-layer co-laminated substrate comprising a stainless steel layer (e.g. for constituting the inner surface of the article) and an anodised or non-anodised layer of aluminium or an aluminium alloy for constituting the outer surface of the article.

[0161] Advantageously, the surface of the face (2a) of the metal substrate (2) has an arithmetic mean roughness Ra greater than or equal to 1 μm.

[0162] The arithmetic mean roughness Ra is measured using a roughness meter according to standard ISO 4287. Ra is the arithmetic mean of the deviations from the mean. The surface topography can be investigated in particular using a profilometer with a probe provided with a fine needle equipped with a diamond tip, or with an optical metrology device, such as The confocal color sensor allows contactless measurement. Studying the surface topography allows the determination of the arithmetic mean roughness Ra.

[0163] Silicone resin

[0164] In the body of the specification, the expression "silicone resin" is used interchangeably to refer to silicone before or after it is crosslinked. In the body of the specification, the expression "silicone" refers to organopolysiloxane materials. Crosslinking is the step of converting the silicone into an insoluble material, for example by polyaddition, polycondensation or dehydrogenation. Crosslinking is carried out using precursors, usually silicone oils or resins, which crosslink to obtain a three-dimensional network, forming the material referred to as silicone resin in the specification.

[0165] This crosslinking can be performed by thermal activation or chemical activation using a catalyst such as platinum.

[0166] The silicone resins can be obtained from precursors that are advantageously soluble in solvents or in emulsions in water, such as crosslinkable oils or resins, in particular chosen from: silanes, silicone oil resins containing at least one vinyl group (-CH=CH2), silicone or silicone-polyester resins (copolymers) containing at least one alkoxy group, such as methoxy or ethoxy, and / or silicone or silicone-polyester resins (copolymers) containing at least one alkoxy group, in particular ethoxy or hydroxyl, and mixtures thereof. These precursors can be crosslinked in order to obtain silicone resins characterized by their insolubility and their substantially solid form.

[0167] Advantageously, these precursors are polymers or oligomers, or in the form of silicone oils with variable branching, or in the form of silicone resins or silicone resin copolymers such as silicone-polyesters, silicone-alkyd resins, silicone-polyurethanes or silicone-epoxy resins with variable pre-crosslinking, or in the form of mixtures of silicone oils, silicone resins and silicone resin copolymers. The silicon atoms may be substituted by alkyl (especially methyl) or aryl (especially phenyl) groups or mixtures thereof. The oil or resin preferably contains one or more (2, 3 or more) hydroxyl or alkoxy (especially methoxy, ethoxy, butoxy) functional groups as substituents for the silicon atoms.

[0168] Advantageously, the silicone resin obtained after crosslinking of its precursors, i.e. crosslinking, is chosen from methyl silicone resins and / or phenyl silicone resins and / or methyl-phenyl silicone resins, methyl silicone-polyester resins (copolymers), phenyl silicone-polyester resins (copolymers), methyl-phenyl silicone-polyester resins (copolymers), silicone-alkyd resins (copolymers), modified silicone resins and mixtures thereof.

[0169] Advantageously, the silicone resin is selected from the group consisting of methyl silicone resin and / or phenyl silicone resin and / or methyl-phenyl silicone resin or methyl silicone-polyester resin (copolymer), phenyl silicone-polyester resin (copolymer), methyl-phenyl silicone-polyester resin (copolymer), silicone-alkyd resin (copolymer), modified silicone resin and mixtures thereof.

[0170] The silicone resin can be obtained from a precursor, which is particularly chosen from: silanes, silicone resins containing at least one vinyl group (-CH=CH2), silicone-polyester resins (copolymers) containing at least one methoxy group and / or silicone-polyester resins (copolymers) containing at least one ethoxy group, and mixtures thereof.

[0171] The monolayer (3) of the silicone resin forms a network which may consist of a combination of four simple organosiloxane units denoted M, D, T and Q depending on the degree of substitution of silicon atoms by oxygen, as described in the table below, wherein R is an organic substituent as described below.

[0172]

[0173] Organopolysiloxane materials or polymers are obtained by crosslinking precursors, which may be monomers or polymers, or, intermediately, oligomers. Organopolysiloxane polymers may also be obtained from mixtures of these different types of precursors. The crosslinking density is higher when the network contains a greater number of T and Q units than D units. The distribution between the M, D, T and Q units depends on the chemical structure of the precursors, in particular on the distribution M, D, T, Q in the precursors.

[0174] The polymer precursor is an organopolysiloxane. These macromolecules are formed from the M, D, T and / or Q units described in the table, wherein R is independently an alkyl group, especially a methyl group, or an aryl group, especially a phenyl group, and different types of R can exist on the same macromolecule.

[0175] Organopolysiloxanes can be linear or slightly branched (mainly D groups), or branched or very branched (mainly T and Q groups). Straight-chain or slightly branched organopolysiloxanes are generally liquid, more or less viscous at room temperature, and are referred to as silicone oils. Branched or highly branched (pre-crosslinked) organopolysiloxanes form networks on the scale of individual macromolecules and are referred to as silicone resins. At room temperature, the resins are essentially in solid form, or in liquid form, provided that, in particular, they have a fairly low molecular weight, in the form of solutions in solvents or in the form of aqueous emulsions. They can be copolymerized with silicon-free organic polymers or oligomers, in particular selected from polyesters, acrylic resins, alkyd resins, polyurethanes and epoxy resins.

[0176] When the crosslinking is a hydrolysis-polycondensation: it is carried out via the hydroxyl or alkoxy functional groups present on the organopolysiloxane, in particular the methoxy, ethoxy or butoxy groups.

[0177] When the crosslinking is polyaddition (or hydrosilylation): it is carried out by reaction between vinyl reactive functional groups (-CH=CH2) present on one of the organopolysiloxanes and hydrosilane (Si-H) reactive functional groups present on the other organopolysiloxane mixed with the first organopolysiloxane.

[0178] All of these reactive functional groups are present in at least one number on each organopolysiloxane, and may be present in 2, 3 or more numbers as long as the molecular structure permits. Silicone oils containing at least one reactive functional group are referred to as "reactive oils". The reactive functional groups may be at the end (terminated) of the macromolecular chain, or distributed throughout the chain.

[0179] The silicone-polyester resin has, in particular, a silicone / polyester mass ratio of, for example, 90 / 10, 80 / 20, 70 / 30, 60 / 40, 50 / 50, 40 / 50, 30 / 70, 20 / 80, 10 / 90, advantageously between 80 / 20 and 50 / 50.

[0180] Linear PDMS silicone oils, pure or pre-emulsified in water, are characterized first by their molecular weight, which is a direct increasing function of the viscosity of the pure oil. They are then characterized by the presence or absence of reactive functional groups, such as hydroxyl functional groups on the silicon atoms (silanols), their number and their position on the molecular chain. For example, reactive oils with viscosities between 50 and 20000 MPa.s, in particular between 300 and 5000 MPa.s, can be used, which have at least one reactive functional group, preferably at least 2, which functional groups can be located at the chain ends.

[0181] The polymer precursors that react by addition polymerization may include, for example, polymethylhydrogensiloxane, vinylmethylsiloxane, vinyl terminated, especially linear polydimethylsiloxane (PDMS), vinyl terminated diphenylsiloxane-dimethylsiloxane copolymers, hydride terminated polydimethylsiloxane, hydride terminated polyphenylmethylsiloxane, cyclic vinylmethylsiloxane, vinyl MQ resin, trimethylsilyl terminated polymethylhydrogensiloxane, methylhydrogensiloxane and trimethylsiloxane terminated dimethylsiloxane copolymers, MQ resin hydrides, and the like, and combinations thereof.

[0182] The polymer precursors that react by hydrolysis-polycondensation, whether they are silicone resins or silicone oils, may include, for example, poly(methylsilsesquioxane), poly(propylsilsesquioxane), poly(phenylsilsesquioxane), polydimethylsiloxane (PDMS), trimethylsilyl-terminated polydimethylsiloxane (PDMS), hydroxyl-terminated polydimethylsiloxane (PDMS), silanol-terminated polyphenylsiloxane (PDMS), silanol-terminated diphenylsiloxane-dimethylsiloxane copolymers, poly(2-acetoxyethylsilsesquioxane), organic-modified alkoxysilanes and their oligomers and all similar macromolecules, and mixtures thereof.

[0183] The organopolysiloxane material or polymer can also be obtained by crosslinking a mixture of one or more monomer precursors and one or more polymer precursors as described above and one or more oligomeric precursors, which can be linear, branched or cyclic. These oligomeric precursors have a lower molecular weight than the polymer precursors. Polymers and / or oligomeric precursors containing more than 2, advantageously much more than 2, of the above-mentioned reactive functional groups can be added to the mixture as "co-binders" to promote the high crosslinking density of the organopolysiloxane polymer finally obtained.

[0184] The monomers, oligomers and / or polymer precursors, especially silicone resins, copolymerized or not copolymerized with the organic polymers act as polymeric binders to obtain solid organopolysiloxane polymers that are bonded to the thermoplastics of the layers.

[0185] If the silicone type organopolysiloxane precursor oil is added to the overall formulation of the layer in a small amount (typically 0.1 to 5% by dry weight), it can be considered an additive independent of the other components used to form the solid organopolysiloxane polymer.

[0186] Crosslinking may require a catalyst:

[0187] In the case of organopolysiloxanes crosslinked by hydrolysis-polycondensation, the formula may include metal catalysts, for example metal complexes based on platinum, tin, zinc, zirconium and cerium, in particular platinum-cyclovinylmethyl-siloxane complexes, tin ethylhexanoate complexes, zinc ethylhexanoate complexes, zirconium ethylhexanoate complexes, cerium ethylhexanoate complexes and dibutyltin laurate complexes.

[0188] In the case of crosslinking of the organopolysiloxane by hydroalkylation, it may be necessary to add a catalyst; this may be, for example, platinum or a suitable platinum-based catalyst, such as a Karstedt catalyst or an Ashbys catalyst.

[0189] Crosslinkers may be present, bearing for example Si-H bonds.

[0190] According to one embodiment, the proportion of the silicone resin in the layer ( 3 b ) is greater than or equal to 20% by weight, respectively, relative to the total weight of the layer ( 3 b ).

[0191] According to another embodiment, the proportion of silicone resin in the layer ( 3 b ) is greater than or equal to 40% by weight, respectively, relative to the total weight of the layer ( 3 b ).

[0192] According to a further embodiment, the proportion of the silicone resin in the layer (3b) is greater than or equal to 50% by weight, respectively, relative to the total weight of the layer (3b).

[0193] According to one embodiment, the proportion of silicone resin in the layer ( 3 c ) is greater than or equal to 20% by weight, respectively, relative to the total weight of the layer ( 3 c ).

[0194] According to another embodiment, the proportion of silicone resin in the layer ( 3 c ) is greater than or equal to 40% by weight, respectively, relative to the total weight of the layer ( 3 c ).

[0195] According to a further embodiment, the proportion of the silicone resin in the layer (3c) is greater than or equal to 50% by weight, respectively, relative to the total weight of the layer (3c).

[0196] According to one embodiment, the proportion of silicone resin in layer (3ab) is greater than or equal to 20% by weight, respectively, relative to the total weight of layer (3ab).

[0197] According to another embodiment, the proportion of silicone resin in layer (3ab) is greater than or equal to 40% by weight, respectively, relative to the total weight of layer (3ab).

[0198] According to a further embodiment, the proportion of the silicone resin in the layer (3ab) is greater than or equal to 50% by weight, respectively, relative to the total weight of the layer (3ab).

[0199] Thermoplastic polymers

[0200] Advantageously, the thermoplastic polymer is selected from the group consisting of polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyamideimide (PAI), polyimide (PI), polyphenylene ether (PPO), polyarylether sulfide (PAS), polyetherimide (PEI), polybenzimidazole (PBI), liquid crystal polymer (LCP), polyphenylene sulfide (PPS), polyaryletherketone (PAEK), including polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK), polyetherketoneetherketoneketone (PEKEKK), and mixtures thereof.

[0201] Heterocyclic thermoplastic polymers

[0202] Suitable examples of heterocyclic thermoplastic polymers according to the present invention include polyetherimide (PEI), polyimide (PI), polyamide-imide (PAI) and polybenzimidazole (PBI) or mixtures thereof.

[0203] PAEK

[0204] Advantageously, the polyaryletherketone (PAEK) is selected from the group consisting of polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK), particularly preferably PEEK.

[0205] Advantageously, the nature of the thermoplastic polymers in layers (3b) and (3c) may be the same or different.

[0206] Advantageously, the layer (3b) comprises one or more thermoplastic polymers, preferably in a proportion by weight of less than 30%, preferably less than 20% of said layer.

[0207] Advantageously, the layer (3c) comprises one or more thermoplastic polymers, preferably in a proportion by weight of less than 50%, preferably less than 40% of said layer.

[0208] Advantageously, the layer (3ab) comprises one or more thermoplastic polymers, preferably in a proportion by weight of less than 50%, preferably less than 40% of said layer.

[0209] According to one embodiment, layer (3b) and layer (3c) comprise one or more thermoplastic polymers, the proportion of thermoplastic polymer in layer (3c) being preferably greater than the proportion of thermoplastic polymer in layer (3b).

[0210] According to another embodiment, layer (3b) and layer (3c) comprise one or more thermoplastic polymers, the proportion of thermoplastic polymer in layer (3b) being greater than the proportion of thermoplastic polymer in layer (3c).

[0211] filler

[0212] Fillers for the purposes of the present invention make it possible to provide mechanical reinforcement and also provide hydrophobicity, while improving the mechanical strength and thermal conductivity of the coating.

[0213] Fillers do not have the sole function of providing color to the coating, but may contribute to it.

[0214] The presence of fillers with excellent thermal conductivity can compensate for the low thermal conductivity of PAEK polymer.

[0215] Advantageously, the filler is selected from the group consisting of ceramic fillers (SiO2, etc.) and / or mineral and / or metallic fillers (Al2O3, TiO2, etc.) and / or silica and / or diamond particles.

[0216] Preferably, the filler is selected from the group consisting of metal oxides, metal carbides, metal oxynitrides, metal nitrides and mixtures thereof.

[0217] Advantageously, the metal is a transition metal, for example at least one of the elements selected from B, Ni, Ti, Zr or Hf.

[0218] More preferably, the filler is selected from the group consisting of:

[0219] - Reinforcing filler: organic or inorganic hard filler; the inorganic hard filler preferably has particles of silicon carbide or aluminum oxide or zirconium oxide, or graphite, or ceramics, or carbonates, or aluminum oxide hydrates, aluminum hydroxide or one or more metal oxides, or graphene;

[0220] - other reinforcing fillers chosen from metal oxides: silica, mica, lamellar fillers, clays such as montmorillonite, sepiolite, gypsum, kaolinite and laponite, zinc dioxide, quartz and zirconium phosphate, aluminum oxide, zirconium oxide, zinc oxide, copper oxide and iron oxide;

[0221] - fillers chosen from reinforcing fibers: glass, carbon or aramid fibers;

[0222] - a conductive filler comprising a transition metal carbide and / or a transition metal nitride: characterized in that the transition metal is at least one element selected from B, Ni, Ti, Zr or Hf;

[0223] For example: cubic boron nitride, diamond particles, metal particles;

[0224] -Layered fillers capable of imparting lubricating properties, such as clay, graphene or graphite.

[0225] Preferred fillers for bonding with organopolysiloxanes are:

[0226] - reinforcing fillers: silica or carbonates, the filler content being at least 10-15% by weight and at most 60% by weight;

[0227] - Alumina, alumina hydrate, aluminum hydroxide;

[0228] - silicon dioxide (precipitated or pyrogenic), D50<0.1 μm, BET surface area>30 m2 / g, preferably between 30 and 500 m2 / g;

[0229] -Mixtures of quartz and silicon dioxide, diatomaceous earth or quartz powder, titanium, mica, talc, kaolin, barium sulfate, slaked lime, zinc oxide, expanded vermiculite, unexpanded vermiculite, calcium carbonate, etc.

[0230] More preferably, the filler is selected from the group consisting of alumina, silicon carbide, tungsten carbide, boron nitride, quartz, and mixtures thereof.

[0231] Advantageously, the filler present in the sublayer ( 3 a ) is an inorganic hard filler, preferably an oxide, a carbide, a metal nitride, preferably aluminum oxide, silicon carbide or pyrogenic silicon dioxide.

[0232] Certain inorganic hard fillers such as silicon carbide, in addition to their mechanical reinforcement properties, have the advantage of being electrically conductive fillers, thus providing excellent thermal conductivity.

[0233] The addition of this type of filler makes it possible to improve the cooking results, with a better diffusion of heat from the metal base to the food in contact with the coating.

[0234] Advantageously, the average diameter D50 of the filler is comprised between 0.1 and 50 μm, more advantageously between 5 and 15 μm.

[0235] Advantageously, the proportion of filler in the layer is comprised between 0.5 and 30% by dry weight, preferably between 5 and 20% by dry weight, relative to the total weight of said layer after curing.

[0236] Advantageously, the proportion of filler in layer (3a) is greater than 20% by weight, preferably greater than 30% by weight, relative to the total weight of said layer.

[0237] Advantageously, the proportion of filler in layer ( 3 c ) is less than 10% by weight relative to the total weight of said layer.

[0238] Advantageously, the proportion of filler in layer (3ab) is less than 10% by weight relative to the total weight of said layer.

[0239] Advantageously, the proportions of fillers in layers (3a), (3ab), (3b) and (3c) may be the same or different.

[0240] Advantageously, the nature of the fillers in layers (3a), (3ab), (3b) and (3c) may be the same or different.

[0241] additive

[0242] Advantageously, the additive is selected from the group consisting of defoamers, dispersants, wetting agents, thickeners, pH adjusters and reactive silicone oils.

[0243] The defoamer is preferably selected from mineral oils, glycols, hydrocarbons, glycerides, ethylene oxide and emulsified fatty acids.

[0244] The surfactant is preferably selected from glycol ethers, ethoxylated alcohols other than alkylphenol ethoxylates (APE), gemini surfactants.

[0245] The dispersant is preferably selected from the group consisting of anionic dispersants, such as fatty acid derivatives.

[0246] The thickener is preferably selected from the group consisting of acrylic or polyurethane based copolymers, cellulose and fumed silica.

[0247] The pH adjuster is preferably selected from the group consisting of Bronsted bases: ammonia, amines (triethylamine, triethanolamine, etc.), hydroxides (sodium hydroxide, potassium hydroxide, etc.) and carbonates.

[0248] Advantageously, the proportion of additives in layer (3a) is less than 1% by weight relative to the total weight of said layer.

[0249] Advantageously, the proportion of additives in layer (3c) is less than 20% by weight relative to the total weight of said layer.

[0250] Advantageously, the proportion of additives in layer (3ab) is less than 20% by weight relative to the total weight of said layer.

[0251] Colorants

[0252] Advantageously, the colorant is chosen from thermochromic pigments, heat-stable pigments, flakes, preferably holographic flakes, and mixtures thereof.

[0253] Advantageously, the proportion of colorant in layer ( 3 b ) and layer ( 3 c ) is comprised between 0.5 and 50% by dry weight relative to the total weight of said layer after curing.

[0254] Advantageously, the proportion of colorant in layer (3b) ranges from 10% to 40% by weight relative to the total weight of said layer.

[0255] Advantageously, the proportion of colorant in layer (3c), when present, is less than 10% by weight relative to the total weight of said layer.

[0256] Advantageously, the proportions of colorants in layers (3b) and (3c) may be the same or different.

[0257] Advantageously, the nature of the colorants in layers (3b) and (3c) may be the same or different.

[0258] Thermochromic Pigments

[0259] Preferably, the thermochromic pigment is selected from Bi2O3, Fe2O3, V2O5, WO3, CeO2, In2O3, Y 1.84 Ca 0.16 Ti 1.84 V 0.16 O 1.84 、AgI、(Bi 1-x A x )(V 1-y M y )O4, where

[0260] - x is equal to 0 or x is between 0.001 and 0.999 included;

[0261] - y is equal to 0 or y is between 0.001 and 0.999;

[0262] - A and M are selected from the group consisting of nitrogen, phosphorus, alkali metals, alkaline earth metals, transition metals, poor metals, semimetals or lanthanides;

[0263] -A and M are different from each other.

[0264] It is known that A and M are different from each other, at this time:

[0265] - A is an alkali metal, which may be selected from Li, Na, K, Rb and Cs;

[0266] - M is an alkali metal, which may be selected from Li, Na, K, Rb and Cs;

[0267] - A is an alkaline earth metal, which may be selected from Be, Mg, Ca, Sr and Ba;

[0268] - M is an alkaline earth metal which may be selected from Be, Mg, Ca, Sr and Ba;

[0269] - A is a transition metal which may be selected from Sc, Ti, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Ta, W and Ir;

[0270] - M is a transition metal which may be selected from Sc, Ti, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Ta, W and Ir;

[0271] - A is a poor metal, which can be selected from Al, Zn, Ga, In and Sn;

[0272] - M is a poor metal, which can be selected from Al, Zn, Ga, In and Sn;

[0273] - A is a semimetal, which can be selected from B, Si, Ge and Sb;

[0274] - M is a semimetal, which can be selected from B, Si, Ge and Sb;

[0275] - A is a lanthanide element, which may be selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu;

[0276] - M is a lanthanide element, which can be selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu.

[0277] Preferably, A and M are different from each other and are B and / or Mg.

[0278] Preferably, the pigment (Bi 1-x A x )(V 1-y M y )O4 has a monoclinic scheelite crystal form at room temperature.

[0279] Preferably, x and y are equal to 0, that is, the pigment (Bi 1-x A x )(V 1-y M y )O4 is bismuth vanadate (BiVO4). Advantageously, BiVO4 having a monoclinic scheelite crystal structure at room temperature is used.

[0280] Bismuth vanadate is a yellow inorganic compound with the formula BiVO4, which is widely used due to its coloring properties and non-toxicity. Recorded in the Colour Index International database as QIPigment Yellow 184, it is produced in particular by the company Heubach BASF FERRO (Lysopac) or Bruchaler Farbenfabrik sell.

[0281] Heat stable pigments

[0282] Preferably, the heat stable pigment is selected from the group consisting of:

[0283] -Rutile titanium yellow pigments;

[0284] Yellow pigments derived from bismuth, for example selected from stabilized bismuth vanadate (Py184);

[0285] - red pigments, for example selected from perylene red (for example PR149, PR178 and PR224), iron oxide;

[0286] -Bismuth oxyhalide type orange pigment (PO 85 );

[0287] -Bismuth vanadate orange pigment (PO 86 );

[0288] -Zinc Tin Titanium Orange Pigment (PO 82 );

[0289] -Cerium sulfide orange pigment (PO 75 PO 78 );

[0290] -Rutile antimony titanium chrome orange pigment (PBr 24 );

[0291] -Rutile Tin and Zinc Orange Pigments (Py 216 );

[0292] -Orange-yellow niobium oxide tin zinc sulfide pigment (Py 227 );

[0293] -Double tin and niobium oxide orange-yellow pigments;

[0294] -Co3(PO4)2;

[0295] -LiCoPO4;

[0296] -CoAl2O4;

[0297] -Cr2O3;

[0298] -TiO2;

[0299] -Black Pigment PBk28 (Copper Chromite Black Spinel)

[0300] - and mixtures thereof.

[0301] decorate

[0302] According to one embodiment, the layer (3b) is continuous and covers the entire layer (3a) (see Figure 1 ).

[0303] According to another embodiment, the layer (3b) does not cover the entire layer (3a) and forms at least one decoration (see Figure 2 ).

[0304] Advantageously, the layer (3b) comprises several decorations, one (i) comprising one or more thermochromic pigments and another (j) comprising at least one reference temperature pigment composition (cf. Figure 3 ).

[0305] According to one embodiment, each of the two decorations (i) and (j) is in the form of adjacent non-overlapping patterns. For example, each decoration is represented by different geometric patterns evenly distributed over the entire surface and alternating relative to each other (see Figure 4 A).

[0306] According to another embodiment, the two decorations (i) and (j) partially overlap. For example, each decoration is represented by a different geometric pattern evenly distributed over the entire surface and partially overlapping (see Figure 4 B).

[0307] Preferably, the two decorations (i) and (j) overlap, either because one of the two decorations is a continuous layer and the other decoration covers the continuous layer in the form of a pattern, or because the two decorations (i) and (j) are in the form of overlapping patterns (see Figure 4 C).

[0308] Thin slice

[0309] The flakes useful in the present invention may be independently selected from coated or uncoated mica flakes, coated or uncoated silica flakes, coated or uncoated aluminum flakes, and coated or uncoated iron oxide flakes. Titanium dioxide coated mica or silica flakes. The flakes useful in the present invention may be treated to produce specific color effects.

[0310] Advantageously, the flakes are chosen from the group consisting of particles of mica, aluminum, titanium dioxide coated mica or mixtures thereof.

[0311] Holographic Sheets

[0312] Advantageously, the flakes are holographic flakes, ie a mixture of magnetizable particles and non-magnetizable particles.

[0313] The magnetizable particles may advantageously be particles comprising at least one ferromagnetic metal. These magnetizable particles may be homogeneous, i.e. consist of the same material, or composite, i.e. have a core-shell structure, wherein the ferromagnetic metal is located in the core and / or shell of the particles. Examples of composite magnetizable particles include mica flakes coated with iron oxide Fe2O3 or stainless steel fibers coated with a sol-gel material as an anti-corrosion protection during the coating step, or flakes made of a plastic material coated with iron oxide Fe2O3, or flakes whose core is a ferromagnetic metal and whose shell is formed by a plastic material or a sol-gel material.

[0314] According to one embodiment, a portion of said magnetizable particles are oriented to form a three-dimensional decoration.

[0315] Advantageously, the mixture of magnetizable particles and non-magnetizable particles represents between 1% and 5% by weight, preferably between 2% and 3% by weight, of the weight of the layer.

[0316] Advantageously, the percentage of non-magnetizable particles in the mixture of magnetizable and non-magnetizable particles is comprised between 15% and 40% by weight relative to the total weight of the mixture.

[0317] Advantageously, the magnetizable particles have a size D50 less than or equal to 23 μm.

[0318] For the purposes of the present invention, the term "D50" is understood to mean the largest dimension exhibited by 50% by number of the particles.

[0319] Advantageously, the non-magnetizable particles have a dimension D90 comprised between 20% and 250% of the dimension D90 of the magnetizable particles.

[0320] For the purposes of the present invention, the term "D90" is understood to mean the largest dimension exhibited by 90% by number of the particles.

[0321] Advantageously, the magnetizable particles and / or the non-magnetizable particles are colored on the surface.

[0322] Advantageously, the non-magnetizable particles consist of mica, aluminum or mica coated with titanium dioxide. Advantageously, the magnetizable particles consist of iron, iron oxide, iron-coated aluminum or iron-coated mica, the iron being in the form of ferrite.

[0323] Preferred architecture

[0324] Advantageously, the invention relates to a coated cooking element (1) for a cooking appliance or electric cooking utensil, comprising a metal substrate (2) coated on at least one face (2a) with only the following layers, in order starting from the metal substrate (2):

[0325] (3a) an adhesive sublayer comprising between 20 wt% and 100 wt% of one or more polymers (α) selected from the group consisting of polyaryletherketone (PAEK) and one or more polymers selected from the group consisting of polyetherimide (PEI), polyimide (PI), polyamide-imide (PAI) and polybenzimidazole (PBI), based on the total weight of the sublayer, wherein the weight ratio of PAEK:(PEI+PI+PAI+PBI) is comprised between 1:1 and 15:1;

[0326] (3b) optionally one or more intermediate layers, said intermediate layers consisting of one or more colorants and optionally:

[0327] - one or more silicone resins, and / or

[0328] - one or more thermoplastic polymers; and / or

[0329] - one or more fillers; and / or

[0330] - one or more additives,

[0331] (3c) a finishing layer, the finishing layer consisting of one or more silicone resins and optionally:

[0332] - one or more thermoplastic polymers; and / or

[0333] - one or more fillers; and / or

[0334] - one or more additives; and / or

[0335] - Thin flakes.

[0336] The thickness of the adhesive sublayer ( 3 a ) is advantageously comprised between 30 and 60 μm.

[0337] Preferably, the colorant of the intermediate layer (3b) comprises pigments and / or flakes, advantageously holographic.

[0338] According to a variant, the intermediate layer (3b) consists of:

[0339] ● one or more colorants, especially pigments and / or flakes, advantageously holographic;

[0340] one or more thermoplastic polymers, advantageously selected from the group consisting of polyamideimide (PAI), polyimide (PI), polyetherimide (PEI), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyaryletherketone (PAEK) and mixtures thereof,

[0341] 0 to 10% filler;

[0342] 0 to 20% additives;

[0343] ●Optionally one or more silicone resins.

[0344] According to another variant, the intermediate layer (3b) consists of:

[0345] ● one or more colorants, especially pigments and / or flakes, advantageously holographic;

[0346] 0 to 10% filler;

[0347] 0 to 20% additives;

[0348] ● one or more silicone resins; and

[0349] - Optional one or more thermoplastic polymers, advantageously selected from the group consisting of polyamideimide (PAI), polyimide (PI), polyetherimide (PEI), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyaryletherketone (PAEK) and mixtures thereof.

[0350] According to a particular variant, the intermediate layer ( 3 b ) does not comprise silicone resin.

[0351] According to another particular variant, the intermediate layer (3b) consists of:

[0352] ● one or more colorants, especially pigments and / or flakes, advantageously holographic;

[0353] one or more thermoplastic polymers, advantageously selected from the group consisting of polyamideimide (PAI), polyimide (PI), polyetherimide (PEI), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyaryletherketone (PAEK) and mixtures thereof,

[0354] 0 to 10% filler;

[0355] 0 to 20% additives;

[0356] ●One or more silicone resins.

[0357] According to one particular embodiment, the coating comprises two intermediate layers (3b), at least one of which is decorative. Advantageously, the layer (3b) consists of several decorations, one (i) comprising one or more thermochromic pigments and the other (j) comprising at least one reference temperature pigment composition.

[0358] Typically, the thickness of the intermediate layer ( 3 b ) is comprised between 3 μm and 10 μm.

[0359] Preferably, when present, the intermediate layer (3b) only partially covers the base layer (3a).

[0360] Alternatively, according to another embodiment, the coating has no intermediate layer (3b). In this case, the layer (3c) is applied to the layer (3a) or the last layer (3ab).

[0361] According to one embodiment, the finishing layer (3c) consists of one or more silicone resins and optionally one or more thermoplastic polymers.

[0362] According to another embodiment, the finishing layer (3c) consists of one or more silicone resins and one or more thermoplastic polymers.

[0363] Typically, the thickness of the layer ( 3 c ) is comprised between 0.1 μm and 10 μm.

[0364] In a particular embodiment, the average thickness of the adhesive sublayer ( 3 a ) is comprised between 30 and 60 μm, the thickness of the layer ( 3 b ) is comprised between 3 and 10 μm, and the thickness of the layer ( 3 c ) is comprised between 0.1 μm and 10 μm.

[0365] The average thickness of the adhesive sublayer (3a) is, for example, the average of at least 10 measurements, preferably 15 measurements, of the thickness at 10 or 15 random locations.

[0366] method

[0367] Another object of the present invention relates to a method for manufacturing a coated cooking element (1) according to the present invention, comprising the following successive steps:

[0368] i. A step of supplying a metal substrate (2) comprising two opposing surfaces;

[0369] ii. Optionally, a step of treating the face (2a) of the substrate (2) to obtain a treated face (2a) that promotes adhesion of the adhesive sublayer (3a) to the substrate (2);

[0370] iii. depositing one or more continuous layers of an adhesive sublayer (3a) on the face (2a) of the substrate (2);

[0371] iv. Optionally, drying and / or sintering at a temperature of> 400°C;

[0372] v. Optionally, applying a layer (3ab) and / or an intermediate layer (3b);

[0373] vi. Applying a finishing layer (3c);

[0374] vii. Curing at a temperature of 230°C to 420°C.

[0375] Advantageously, the steps of the method according to the invention make it possible to coat a metal substrate (2) with a coating (3) formed by layers (3a), optionally (3ab) and (3b) and (3c). Typically, these layers are wetted during their application. For the purposes of the present invention, a "wetting layer" is understood to mean that the layer contains all or part of its solvent.

[0376] Preferably, all or part of the solvent of the wet layer is removed naturally or by physical treatment, such as thermal drying, drying by a stream of air or by vacuum treatment.

[0377] Advantageously, the coating composition according to the invention may further comprise at least one solvent. Advantageously, the solvent may be protic. Advantageously, the solvent may be non-toxic.

[0378] The solvent that can be used in the coating composition of the present invention may advantageously comprise at least one alcohol, and may preferably be selected from isopropanol, methanol, ethanol, and mixtures thereof.

[0379] The coating is applied in multiple layers. In this case, the deposition of at least one layer of the coating (3) according to the invention on at least one of the two opposite faces of the substrate is repeated several times. Preferably, a drying step is carried out between the application of each layer and then the coated substrate is cured after the application of the last layer. The application of the coating (3) to the substrate (2) by the method according to the invention makes it possible to obtain a thermally stable coating.

[0380] The coating formulation to be applied is usually in aqueous form, with the polymer of the polymer phase being in suspension form. Other non-aqueous solvents are also suitable.

[0381] Advantageously, the method for manufacturing a coated cooking element (1) according to the invention comprises one or more drying steps between 80° C. and 150° C. after application of each of the layers. Drying can be carried out by convection or infrared.

[0382] The coating according to the invention can be applied by the method according to the invention on a flat substrate or on a shaped substrate or on a partially flat area of ​​a shaped substrate. A thermally stable coating is obtained. Typically, the coating is wettable.

[0383] Advantageously, the method for manufacturing a coated cooking element (1) according to the invention comprises a step of shaping said metal substrate (2) before step iii., after step vi., or after curing step vii. Shaping is also known as stamping.

[0384] When the shaping step precedes step iii. of applying the coating, the coating is preferably carried out by spraying.

[0385] When this shaping step follows step vii. of applying the coating, the coating is preferably carried out by screen printing or by roller printing.

[0386] The method according to the invention comprises a step vii. of curing the element obtained in step vii. of the method. For the purposes of the present invention, curing the coated substrate is understood to mean a thermal treatment which makes it possible to densify the coating or coatings applied to the substrate and to crosslink the organopolysiloxane precursor (silicone resin).

[0387] Curing is carried out in step iv. Typically, the curing temperature in step iv. is comprised between 230°C and 420°C.

[0388] Advantageously, the method for manufacturing a coated cookware (1) according to the invention comprises a single final curing step vii. of all applied layers. This single curing step is carried out simultaneously on all applied layers.

[0389] Advantageously, the method for manufacturing a coated cooking element (1) according to the invention comprises a step of shaping said substrate (2) before or after step iii. Shaping is also known as stamping.

[0390] Preferably, the metal substrate (2) in step i) is in the form of a disc, preferably a flat disc, the shaping of which is carried out after the coating has been applied.

[0391] Advantageously, the process according to the invention does not comprise any drying and / or curing step other than that of step (vii).

[0392] The application steps (iii) and (vi) and step (v) of applying layer (3ab) can be carried out by electrostatic powder coating, by spraying in solvent or aqueous phase, by screen printing, by roller printing or by digital printing.

[0393] The step (v) of applying the intermediate layer (3b) can be performed by pad printing, screen printing, inkjet printing or flexographic printing.

[0394] Utensils

[0395] The invention also relates to a cooking utensil (100) comprising a coated cooking element (1).

[0396] According to one embodiment, the cooking appliance (100) has a heating surface (6) for contact with an external heating source, the heating surface (6) being opposite to a cooking surface (5) for contact with food during cooking.

[0397] Advantageously, the cooking appliance (100) according to the invention is selected from the group consisting of a saucepan, a frying pan, a skillet or a fondue pot, a raclette pan, a Dutch oven, a wok, a griddle, a pancake maker, a grill, a broiler, a casserole, a small pot, a rice cooker or a bread machine insert, or a food mould.

[0398] The invention also relates to an electric cooking appliance (200) comprising a coated cooking element (1) according to the invention and a heating source (210) configured to heat the coated cooking element (1).

[0399] Advantageously, the electric cooking appliance (200) is selected from the group consisting of an electric pancake maker, an electric raclette appliance, an electric fondue appliance, an electric grill, an electric frying grill, an electric rice cooker, a bread maker or an electric pressure cooker, a waffle maker, an electric rice cooker and a jam maker.

[0400] The cooking utensil according to the invention may in particular be a cooking utensil in which one of the two opposite faces of the base plate is an inner surface, optionally a concave surface, for being arranged on the face where food is to be introduced into or on the utensil, and in which the other face of the base is an outer surface, optionally a convex surface, for being arranged towards a heat source.

[0401] Non-limiting examples of cooking utensils according to the invention include cooking utensils such as deep-fried and frying pans, sauté pans and stir-fry pans, Dutch ovens and casseroles, pancake makers, baking pans and sheets, grill pans and grills, food preparation bowls, among others.

[0402] Example

[0403] The objects, aspects and advantages of the invention will be better understood from the following description of particular embodiments of the invention given by way of non-limiting example.

[0404] Of course, the present invention is in no way limited to the described and illustrated embodiments, which are provided only as examples. Modifications may still be made without exceeding the scope of protection of the present invention, especially from the perspective of the composition of the various elements or by replacement of technical equivalents.

[0405] 1) Examples of embodiments:

[0406] Raw materials for layer (3a):

[0407] -Heterocyclic polymer resins:

[0408] o Polyamide-imide resin (PAI) at 29% solids in N-butylpyrrolidone (NBP);

[0409] o Resin in powder form: polyamic acid, 90% dry extract in N-methylpyrrolidone (NMP / water), reference SOLVAY, TORLON AI10LS grade;

[0410] o Resin in solvent: 9% polybenzimidazole (PBI) in dimethylacetamide (DMAc).

[0411] -Other aromatic polymer resins:

[0412] o Polyetheretherketone (PEEK) resin powder, Vicote 704 from VICTREX, polymer powder with D50 of 10 μm;

[0413] o PEKK, KEPSTAN 7002PT resin powder from Arkema, D50 20 μm;

[0414] o PEKK, KEPSTAN 6002PT resin powder from Arkema, D50 50μm;

[0415] o Polyethersulfone (PES) resin powder, micronized grade from SOLVAY, polymer powder with D50 of 40 μm.

[0416] - Fluoropolymer resin (pre-dispersed at 20% in PPG with UltraTurrax, 20000 rpm):

[0417] o 3M PTFE powder / DYNEON: TF 9207Z;

[0418] o 3M FEP Powder / DYNEON: 6233pz.

[0419] - Unlabeled polar aprotic solvent (ie non-toxic as defined in the present invention):

[0420] o N-Formylmorpholine (NFM);

[0421] o N-methylimidazole (NMI);

[0422] o N-butylpyrrolidone (NBP).

[0423] -Alcohol solvent

[0424] oPropylene glycol: PPG;

[0425] oDiglycol: Butyl diglycol.

[0426] - Surfactants and defoamers;

[0427] o Tego foamex K7 from Evonik;

[0428] oGenapol X089 from Clariant.

[0429] -Reinforcing fillers:

[0430] o Alumina, CAHP-F240 grade (particle size D50: 50 μm);

[0431] o Silicon carbide, SIKA 400, SIKA 320 grades;

[0432] oFumed silica;

[0433] o MICA MILL200 / 325.

[0434] -pigment:

[0435] oBlack 100;

[0436] oBlue CM13;

[0437] o Red brick perylene (wear indicator);

[0438] Titanium;

[0439] o Talc;

[0440] o Graphite.

[0441] -Acrylic resin:

[0442] o Modarez PW336: 30% acrylic polymer solution in water;

[0443] o Rohagit SD 15: 30% acrylic acid polymer solution in water phase.

[0444] Raw materials for the middle layer (3b and 3b') and the finishing layer (3c):

[0445] -Silicone resin:

[0446] o RS1: ethoxy-functional polyester silicone resin in solvent phase (80% silicone / 20% polyester), viscosity about 2000 mPas at 25°C, solids content = 75%;

[0447] o RS2: ethoxy-functional polyester silicone resin in solvent phase (50% silicone / 50% polyester), viscosity about 2000 mPas at 25°C, solids content = 75%;

[0448] o RS3: ethoxy-functional polyester silicone resin in solvent phase (30% silicone / 70% polyester), viscosity about 2000 mPas at 25°C, solids content = 75%;

[0449] o RS4: methylphenyl functionalized polyester silicone resin in solvent phase, viscosity about 2000 mPas at 25°C, solids content = 75%;

[0450] o RS5: ethoxy-functional polyester silicone resin in solvent phase (50% silicone / 50% polyester), viscosity about 2000 mPas at 25°C, solids content = 75%;

[0451] o RS6: ethoxy-functional methyl organopolysiloxane resin in aqueous emulsion, viscosity about 1500 mPas at 25°C, solids content = 52%.

[0452] -Heterocyclic polymer resins:

[0453] o Polyamide-imide resin (PAI), 29% solids in N-butylpyrrolidone (NBP), Torlon from SOLVAY. - Other aromatic polymer resins:

[0454] o Polyetheretherketone (PEEK) resin powder, Vicote 703 from VICTREX, polymer powder with D50 of 25 μm;

[0455] o Polyetheretherketone (PEEK) resin powder, Vicote 704 from VICTREX, polymer powder with D50 of 10 μm;

[0456] o PEKK, KEPSTAN 7002PT resin powder from Arkema, D50 20 μm;

[0457] o PEKK, KEPSTAN 6002PT resin powder from Arkema, D50 50μm;

[0458] o Polyethersulfone (PES) resin powder, micronized grade from SOLVAY, polymer powder with D50 of 40 μm.

[0459] -Alcohol solvent

[0460] oDipropylene glycol n-butyl ether (DPNB);

[0461] o 2-Methoxy-1-methylethyl acetate (MPA);

[0462] oButanediol acetate (BGA);

[0463] oButyl acetate;

[0464] - Surfactants and defoamers;

[0465] o Mineral oil: Tego Foamex K7 from Evonik

[0466] o Fatty alcohol polyglycol ethers: Genapol X080 from Clariant or TergitolTM N-100X.

[0467] -Reinforcing fillers:

[0468] oFumed silica: Levasil CC301;

[0469] o Post-treated dimethyldichlorosilane fumed silica:

[0470] Aerosil R972.

[0471] -pigment:

[0472] o Mica: IRIODIN 100 or IRIODIN 300 and / or

[0473] Magnapearl 5000;

[0474] o Cr / Fe oxide: Sicopal black K0098FK;

[0475] o Carbon black: Derussol F25 or Cabot Monarch 4750;

[0476] o Perylene red: Paliogen red (PR178);

[0477] o Ferrous oxide: Brick H856.

[0478] -Acrylic resin:

[0479] o Rohagit SD 15: 30% acrylic acid polymer solution in water phase.

[0480] -Silicone oil:

[0481] o Polyether modified polysiloxane: TEGO GLIDE 100;

[0482] o Dimethicone Oil: CT 601M.

[0483] -Other additives:

[0484] o AMP 90: solution of 2-amino-2-methyl-1-propanol: 90% polymer in water, buffer;

[0485] o Metlot368: fatty acid esters;

[0486] o Dolfynox 1030: propoxylated polyethylene glycol ether, wetting agent;

[0487] o Edaplan LA 451: solution of anionic ester in ethanol / water, wetting agent;

[0488] o Tego Glide 407: Methylphenyl polysiloxane, flow agent.

[0489] Operating Principle of Jar Mill (Mechanical Grinding):

[0490] Ball milling involves loading a jar with the sample to be milled and so-called grinding balls and rotating the jar at a certain speed around its axis. A roller press is usually used to rotate the jar. The sample can be dry ground or dispersed in a suitable solvent (e.g. water or alcohol). The dispersion may also contain certain adjuvants (such as dispersants or defoamers).

[0491] The median diameter of the grinding balls must be adapted to the size of the particles to be ground. The finer the particles, the smaller the diameter of the balls used. The total volume of the balls including the voids between the balls will account for approximately 50-60% of the internal volume of the jar. The balls of different sizes are advantageously distributed according to the following weight proportions relative to the total weight of the balls: small balls 25%, medium balls 50%, large balls 25%. The size of the smallest balls is between 2 and 10 mm. Alumina and stabilized zirconium oxide are generally used as materials for the balls.

[0492] Examples of embodiments of the cooking appliance according to the invention:

[0493] On a shaped aluminium disk (30 cm in diameter) previously degreased and sandblasted to obtain a roughness of 4 to 7 μm (Ra), a continuous layer 3a of a base layer composition (3a1 to 3a4) selected from the following is deposited by spraying:

[0494] Layer 3a:

[0495] Layer 3a1:

[0496] An aqueous semi-finished composition SF1 was prepared based on a heterocyclic polymer with an amine and an unlabeled polar aprotic solvent.

[0497] An aqueous semi-finished composition SF1 was prepared containing the following compounds in the amounts indicated below:

[0498] PAI resin at 29% solids in NBP 327.9g NBP 117.7g Triethylamine 32.8g Desalinated water 521.6g total 1000.0g

[0499] The implementation of PAI includes the step of entering the water phase through the preparation of polyamide-AMIC acid salt. The process was carried out in a brand ball mill at room temperature in the presence of amines.

[0500] The characteristics of the aqueous composition SF1 thus obtained are as follows:

[0501] - Theoretical dry extract: 9.5%;

[0502] -Dry extract measured in the composition: 9.3%

[0503] The preparation of the semi-finished composition SF2 was carried out in a ball mill for 20 minutes to obtain the following mill paste, which was designated as SF2.

[0504]

[0505] Composition of sublayer 3a1

[0506] The final step is carried out in a Rayneri type disperser, resulting in the following bonding sublayer:

[0507]

[0508] The properties of the obtained sub-layer 3a1 are as follows:

[0509] -The final mass ratio of the polymer resin mixture is as follows: PEEK / PAI / PES /

[0510] Filler / Acrylic / Pigment: 19 / 3 / 23 / 30 / 5 / 20;

[0511] - Theoretical dry extract: 41.1%

[0512] - Viscosity measured in AFNOR CA6 cup: 45 seconds.

[0513] The thickness of the layer 3 a 1 is comprised between 50 μm and 100 μm, preferably between 40 μm and 60 μm.

[0514] Layer 3a2:

[0515] The preparation of the semi-finished composition SF3 was carried out in a ball mill for 20 minutes to obtain the following mill paste, which was designated as SF3.

[0516]

[0517]

[0518] Composition of sublayer 3a2

[0519] The final step is carried out in a Rayneri type disperser, resulting in the following bonding sublayer:

[0520]

[0521] The properties of the obtained sub-layer 3a2 are as follows:

[0522] -The final mass ratio of the polymer resin mixture is as follows: PEEK / PAI / PES /

[0523] Filler / Acrylic / Pigment: 17 / 3 / 25 / 30 / 5 / 20;

[0524] - Theoretical dry extract: 42.4%

[0525] - Viscosity measured in AFNOR CA6 cup: 55 seconds.

[0526] The thickness of this layer SCD4 of Example 4 is comprised between 50 μm and 100 μm, preferably between 40 μm and 60 μm.

[0527] Layer 3a3:

[0528] The preparation of the semi-finished composition SF4 was carried out in a ball mill for 20 minutes to obtain the following mill paste, which was designated as SF4.

[0529]

[0530]

[0531] Composition of sublayer 3a3

[0532] The final step is carried out in a Rayneri type disperser, giving the following hard sublayer:

[0533]

[0534] The properties of the obtained sub-layer 3a3 are as follows:

[0535] -The final mass ratio of the polymer resin mixture is as follows:

[0536] PEEK / PAI / PES / :75 / 5 / 20;

[0537] - Theoretical dry extract: 38.5%;

[0538] -Viscosity measured in AFNOR CA6 cup: 1 min 40 sec.

[0539] The thickness of this layer SCD6 of Example 6 is comprised between 50 μm and 100 μm, preferably between 40 μm and 60 μm.

[0540] Layer 3a4:

[0541] The preparation of the semi-finished composition SF5 was carried out in a ball mill for 20 minutes to obtain the following mill paste, which was designated as SF5.

[0542]

[0543] The composition of the sublayer 3a4 was carried out in a Rayneri type disperser, giving the following hard sublayer:

[0544]

[0545]

[0546] The properties of the obtained sub-layer 3a4 are as follows:

[0547] -The final mass ratio of the polymer resin mixture is as follows:

[0548] PEEK / PAI / filler / acrylic resin / pigment: 42 / 3 / 30 / 5 / 20

[0549] - Theoretical dry extract: 41.0%;

[0550] - Viscosity measured in AFNOR CA6 cup: 55 seconds.

[0551] The thickness of the layer SCD9 of Comparative Example 3 is comprised between 50 μm and 100 μm, preferably between 40 μm and 60 μm.

[0552] Middle layer (3b)

[0553] Successive layers (3b) are then deposited by spraying on one of the layers (3a) from the layer composition selected as follows: layer 3b1, layer 3b2 and layer 3b3:

[0554]

[0555]

[0556]

[0557]

[0558] The aqueous composition of layer 3b is prepared according to the ball milling principle. As mentioned above, ball milling is carried out in a tank. The sample can be dry ground or dispersed in a suitable solvent (e.g. water, alcohol or solvent). The dispersion may also contain certain adjuvants (e.g. dispersants or defoamers).

[0559] The thickness of this layer 3 b is comprised between 10 μm and 20 μm, preferably between 12 μm and 15 μm.

[0560] Intermediate layer (3b') and finishing layer (3c)

[0561] As described above, the substrate to which the layer 3a and the continuous layer 3b were applied was coated with a multilayer non-stick coating consisting of an intermediate layer 3b' (6-8 μm) and a finishing layer 3c (14-18 μm) dried for 4 minutes at 100° C. After the deposition of the layers, the entire mixture was finally heated at 250° C. for 1 hour, i.e. the process included only one curing step.

[0562] The composition of the intermediate layer 3b' is deposited by spraying and is as follows: layer 3b'1 and layer 3b'2:

[0563]

[0564]

[0565]

[0566]

[0567] The composition of the finishing layer 3c is deposited by spraying and is as follows: Layers 3c1 to 3c10:

[0568]

[0569]

[0570]

[0571]

[0572]

[0573]

[0574]

[0575]

[0576]

[0577]

[0578]

[0579]

[0580]

[0581] Method for evaluating the performance of non-stick coatings: Egg performance test

[0582] The method for evaluating the non-stick coating properties was carried out using the egg test adapted from paragraph 3.3.2 of AFNOR NF D 21-511 and was performed as follows:

[0583] Clean the sample and wipe any remaining water from the surface.

[0584] The inner surface of the container body is dried in advance.

[0585] Heat the cookware on a gas hob to a temperature between 140 and 170°C.

[0586] The non-stick properties of the cookware were evaluated by breaking a caliber [French size label] 60 / 65 egg and pouring it in the center onto the hot cookware and allowing the egg to set (6-9 minutes); removing the egg from the cookware with a spatula and cleaning the coating with a damp vegetable-based sponge, then recording:

[0587] Score 100: The egg is completely removed with a plastic spatula;

[0588] Rating 75: The egg cannot be completely removed, but the coating can be easily cleaned with a damp sponge;

[0589] Rating 50: The egg cannot be completely removed, but the coating can be cleaned with a damp sponge;

[0590] Score 25: The egg cannot be completely removed and the coating cannot be cleaned with a wet sponge;

[0591] Rating 0: The egg cannot be removed and the coating cannot be cleaned with a wet sponge.

[0592]

[0593] All silicone-polyester resin-based coatings of the present invention have good non-stick properties while adhering to metal.

Claims

1. A coated cooking element (1) for a cooking utensil or electric cooking utensil, comprising a metal substrate (2) coated on at least one side (2a) with at least the following layers, in order starting from the metal substrate (2): (3a) an adhesive sublayer comprising between 20 wt% and 100 wt% of one or more polymers (α) selected from the group consisting of polyaryletherketone (PAEK) and one or more polymers selected from the group consisting of polyetherimide (PEI), polyimide (PI), polyamide-imide (PAI) and polybenzimidazole (PBI), based on the total weight of the sublayer, wherein the weight ratio of PAEK:(PEI+PI+PAI+PBI) is comprised between 1:1 and 15:1; (3b) optionally one or more intermediate layers, said intermediate layers consisting of one or more colorants and optionally: - one or more silicone resins, and / or - one or more thermoplastic polymers; and / or - one or more fillers; and / or - One or more additives. (3c) a finishing layer, the finishing layer consisting of one or more silicone resins and optionally: - one or more thermoplastic polymers; and / or - one or more fillers; and / or - one or more additives; and / or - Thin flakes.

2. The coated cooking element (1) according to claim 1, characterized in that The adhesive sublayer (3a) includes one or more polymers (β) selected from the group consisting of polyphenylene sulfide (PPS) and polyethersulfone (PES).

3. The coated cooking element (1) according to claim 2, characterized in that The adhesive sublayer (3a) comprises at least 20 wt%, preferably at least 25 wt%, of one or more polymers (β), based on the total weight of the sublayer, the polymer (β) being selected from the group consisting of polyphenylene sulfide (PPS) and polyethersulfone (PES).

4. The coated cooking element (1) according to any one of the preceding claims, characterized in that The adhesive sublayer (3a) accounts for less than 40% by weight, preferably less than 30% by weight, preferably 5 to 25% by weight of the total weight of the filling sublayer.

5. The coated cooking element (1) according to claim 2, characterized in that The filler of the bonding sublayer (3a) is selected from the group consisting of metal oxides, carbides, nitrides, preferably aluminum oxide, silicon carbide or pyrogenic silicon dioxide.

6. The coated cooking element (1) according to any one of the preceding claims, characterized in that The adhesive sublayer (3a) comprises one or more acrylic resins.

7. The coated cooking element (1) according to any one of the preceding claims, characterized in that The bonding sublayer (3a) comprises one or more colorants.

8. The coated cooking element (1) according to any one of the preceding claims, characterized in that The polyaryletherketone (PAEK) is selected from the group consisting of polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK).

9. The coated cooking element (1) according to any one of the preceding claims, characterized in that The polymer (α) is selected from the group consisting of polyetheretherketone (PEEK) and polyamide-imide (PAI).

10. The coated cooking element (1) according to any one of the preceding claims, characterized in that The colorant is selected from the group consisting of thermochromic pigments, heat stable pigments, flakes, preferably holographic flakes, and mixtures thereof.

11. The coated cooking element (1) according to claim 10, characterized in that The thermochromic pigment is selected from Bi2O3, Fe2O3, V2O5, WO3, CeO2, In2O3, Y 1.84 Ca 0.16 Ti 1.84 V 0.16 O 1.84 , AgI, (BI 1-x A x )(V 1-y M y )O4, among which - x is equal to 0 or x is between 0.001 and 0.999 included; - y is equal to 0 or y is between 0.001 and 0.999; - A and M are selected from the group consisting of nitrogen, phosphorus, alkali metals, alkaline earth metals, transition metals, poor metals, semimetals or lanthanides; -A and M are different from each other.

12. The coated cooking element (1) according to claim 10 or 11, characterized in that The heat stable pigment is selected from the group consisting of: -Rutile titanium yellow pigments; - yellow pigments derived from bismuth, for example chosen from stabilized bismuth vanadate (Py184); - red pigments, for example selected from perylene red (for example PR149, PR178 and PR224), iron oxide; -Bismuth oxyhalide type orange pigment (PO 85 ); -Bismuth vanadate orange pigment (PO 86 ); -Zinc Tin Titanium Orange Pigment (PO 82 ); -Cerium sulfide orange pigment (PO 75 PO 78 ); -Rutile antimony titanium chrome orange pigment (PBr 24 ); -Rutile Tin and Zinc Orange Pigments (Py 216 ); -Orange-yellow niobium oxide tin zinc sulfide pigment (Py 227 ); -Double tin and niobium oxide orange-yellow pigments; -Co3(PO4)2 -LiCoPO4; -CoAl2O4; -Cr2O3; -TiO2; -Black Pigment PBk28 (Copper Chromite Black Spinel) - and mixtures thereof.

13. The coated cooking element (1) according to any one of claims 10 to 12, characterized in that The holographic flakes are a mixture of magnetizable particles and non-magnetizable particles.

14. The coated cooking element (1) according to any one of the preceding claims, characterized in that The metal substrate (2) is an aluminum, stainless steel, cast iron or cast aluminum, iron, titanium or copper substrate.

15. The coated cooking element (1) according to any one of the preceding claims, characterized in that The layer (3c) comprises one or more thermoplastic polymers, the proportion of thermoplastic polymers in the layer (3c) being less than 50%, preferably less than 40%.

16. The coated cooking element (1) according to any one of the preceding claims, characterized in that The thickness of the adhesive sublayer ( 3 a ) is comprised between 10 and 100 μm, preferably between 20 and 80 μm, preferably between 30 and 60 μm.

17. A method of manufacturing a coated cooking element (1) according to any one of the preceding claims, It is characterized by the following steps: i. A step of supplying a metal substrate (2) comprising two opposing surfaces; ii. Optionally, a step of treating the face (2a) of the substrate (2) to obtain a treated face (2a) that promotes adhesion of the adhesive sublayer (3a) to the substrate (2); iii. depositing one or more continuous layers of the adhesive sublayer (3a) as defined in the preceding claims on the face (2a) of the substrate (2); iv. Optionally, drying and / or sintering at a temperature of> 400°C; v. Optionally, applying a layer (3ab) and / or an intermediate layer (3b); vi. Applying a finishing layer (3c); vii. Curing at a temperature of 230°C to 420°C.

18. The method according to claim 17, characterized in that The sintering temperature is comprised between 400°C and 440°C.

19. A cooking utensil (100) comprising a coated cooking element (1) according to any one of claims 1 to 16.

20. The cooking utensil (100) according to claim 19, characterized in that: The cooking utensil has a heating surface (6) for contacting an external heating source, the heating surface (6) being opposite to a cooking surface (5) for contacting food during cooking.

21. The cooking utensil (100) according to claim 19 or 20, which is selected from the group consisting of a deep-fried pot, a frying pan, a saucepan, a cheese fondue, a raclette, a Dutch oven, a wok, a frying pan, a pancake maker, a grill, a grill, a casserole, a small pot, a rice cooker or a bread machine insert, and a cooking mold.

22. An electric cooking appliance (200) having a coated cooking element (1) and a heating source (210) configured to heat the coated cooking element (1), characterized in that: The coated cooking element (1) is a cooking element according to any one of claims 1 to 16.

23. The electric cooking appliance (200) according to claim 22, selected from the group consisting of an electric pancake maker, an electric raclette appliance, an electric fondue appliance, an electric grill, an electric frying grill, an electric rice cooker, a bread maker or an electric pressure cooker, a waffle maker, an electric rice cooker and a jam maker.

Citation Information

Patent Citations

  • Antiadhesive coating with improved scratch resistance

    US6596380B1

  • Antiadhesive coating with improved Anti-scratch resistance

    WO2000054895A1

  • Antiadhesive coating with improved scratch resistance

    WO2000054896A1

  • Cooking utensil comprising a hard base made from a ceramic and / or metal and / or polymer material and a nonstick coating containing a fluorocarbon resin

    WO2010130954A1